An Analysis of Code Switching Found in the ‎Indonesian Series “My Nerd Girl” - Ramadhana, Humaira; Nurfadhilah, Auliyanti; Mahmud, Murni (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2024)
In an aspect of daily life that involves interactions carried out by one person with another, this can ‎be said to be natural and most likely tends to give rise to various language variations, either in the ‎form of accents or from how they convey something in the same language so that they are ‎connected to each other and understand what people want to convey. Furthermore, humans and ‎language are a unit that cannot be separated because to communicate with other humans it takes a ‎language as a tool that describes a person’s intentions and goals. This is where sociolinguistics ‎functions to learn more about the relationship between social life and society in one scope. Code ‎switching is a language variation by combining words or sentences using several languages in one ‎topic of conversation which aims to facilitate communication. Code switching itself can be applied ‎anytime and anywhere as long as it is adapted to the context. The phenomenon of code switching is ‎very common in everyday life because it can be said that it is already familiar, one of which can be ‎seen in the series “My Nerd Girl”. All the episodes in this series are pretty much shown how some ‎characters relate code switching by using two languages, namely Indonesian and English. ‎Therefore, this series can be considered to be studied in more detail.‎